Seismic Performance Analysis of Multi-Span Simply Supported Bridges - John Sonam; Talkeshwar Ray (International Journal of Scientific Research in Science and Technology, 2024)
Multi-span simply supported (MSSS) bridges are extensively utilized worldwide, yet they often suffer damage or failure during earthquakes. This study employs three-dimensional bridge analysis and design software, CSiBridge, to analyze the seismic response of bridge. The investigation focuses on an existing concrete bridge subjected to the El Centro earthquake ground acceleration. Three distinct underlying soil conditions are considered to assess soil-structure interaction (SSI). Analysis of pier top displacements reveals that bridges with linear horizontal layouts may exhibit minimal displacements and limited impact from soil-structure interaction. However, configurations with irregular horizontal layouts result in notable displacements. This research sheds light on the dynamic behavior of bridges and emphasizes the significance of considering geometric variations in seismic analysis.
Keywords: Multi-Span Simply Supported Bridge; Laminated Rubber Bearing; Dynamic Analysis; Soil-Structure Interaction; Seismic Performance